1980
DOI: 10.1203/00006450-198014010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Effects of Acute Meconium Obstruction on Pulmonary Function

Abstract: SummaryThe relationship between pulmonary function and the migration of meconium to distal airways was determined in 10 rabbits (mean weight 2.6 kg) after insumation of a meconium-saline mixture (1-2 ml/kg). Animals were anesthetized, cannulated, intubated, and mechanically ventilated with 100% oxygen. Lung mechanical dysfunction was most severe during the early phase of meconium migration, 15 min postinsumation. Substantial increases in inspiratory lung resistance (RI) and expiratory lung resistance (RE) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…Tran et al (1 1) instilled large amounts of meconium into the airways of adult rabbits and noticed decreased dynamic compliance during artificial ventilation, but static compliance (determined from pressure-volume recordings) was not influenced. Our results, as well as recent data from in-vitro experiments reported by others (1 5), indicate that the establishment of very low alveolar surface tension at end-expiration-a prerequisite for successful neonatal lung adaptation-might be disturbed by aspiration of meconium at birth. We found that meconium inhibited surfactant function in a concentration-dependent manner both in the pulsatingbubble and in the Wilhelmy-balance system, as indicated by delayed film adsorption and elevated values for minimum and maximum surface tension during cyclic film compression.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Tran et al (1 1) instilled large amounts of meconium into the airways of adult rabbits and noticed decreased dynamic compliance during artificial ventilation, but static compliance (determined from pressure-volume recordings) was not influenced. Our results, as well as recent data from in-vitro experiments reported by others (1 5), indicate that the establishment of very low alveolar surface tension at end-expiration-a prerequisite for successful neonatal lung adaptation-might be disturbed by aspiration of meconium at birth. We found that meconium inhibited surfactant function in a concentration-dependent manner both in the pulsatingbubble and in the Wilhelmy-balance system, as indicated by delayed film adsorption and elevated values for minimum and maximum surface tension during cyclic film compression.…”
Section: Discussionsupporting
confidence: 80%
“…Meconium aspiration syndrome occurs mainly in term and post-term newborn infants, usually as a consequence of intrauterine asphyxia triggering both passage of meconium into the amniotic cavity and fetal gasping (1). Despite recent improvements in immediate postpartum care, including suctioning of the airways and assisted ventilation, intrauterine aspiration of large amounts of meconium remains associated with high mortality (2-4).…”
mentioning
confidence: 99%
“…The heterogeneous aeration and increased functional residual capacity (FRC) seen in MAS may lead to increased alveolar dead space. [2][3][4][5][6] Optimal ventilatory strategy for MAS would avoid/treat pulmonary hypertension and at the same time avoid overventilation of lungs already at risk for overdistention and air leak. It has been demonstrated that volume, rather than pressure, is the important determinant of lung injury 7 and volume targeted ventilation is being increasingly used to ventilate newborn infants.…”
mentioning
confidence: 99%
“…The acute detrimental effects of meconium aspiration on lung function have been well described in many animal models, including the pig, but experimental hemodynamic studies are sparse. [3][4][5][13][14][15][16] Meconium aspiration has been shown to induce pulmonary hypertension in rabbits. 3 Despite a tendency toward increased right ven-tricular systolic pressures, it did not produce significant pulmonary hypertension in prematurely born baboons.…”
Section: Discussionmentioning
confidence: 99%
“…The fatal outcome is frequently associated with persistent pulmonary hypertension, which further contributes to the hemodynamic and respiratory dysfunction. 2 The pathophysiology of the lung injury is still unclear, although hypoxemia, 3,4 pulmonary inflammation, 3,5 surfactant dysfunction, 6 and imbalance in pulmonary vasoregulation 7 have been considered as contributing factors.…”
Section: Introductionmentioning
confidence: 99%